A review of nucleate boiling on nanoengineered surfaces – The nanostructures, phenomena and mechanisms. (October 2019) - Li, Xiangdong; Cole, Ivan; Tu, Jiyuan
Highlights: HTC dominated by microscopic geometrical features. Classic theory not applicable to nanoengineered surfaces. Evaporation-induce negative pressure is critical. Separate liquid and vapor paths are also important. Abstract: Nanostructured surfaces present great potentials to enhance nucleate boiling heat transfer. However, due to the diverse materials and approaches of fabrication, nanostructured surfaces have a wide range of micro/nano-morphologies and different or even conflicting effects on the critical heat flux (CHF) and heat transfer coefficient (HTC), causing serious uncertainties to the design of optimal nanostructures for thermal management. The mechanisms behind the uncertainties are yet to be fully understood. This paper presents a comprehensive review of the nanostructures, bubble dynamics phenomena and boiling heat transfer performance of various nanoengineered surfaces. It is proposed that the evaporation of liquid menisci in nanoscale pores triggers a significant negative pressure in the porous structures, which causes an additional heat and mass transfer mechanism and significantly changes the features of bubble nucleation, growth and departure, as well as the CHF and HTC. However, the effectiveness of the negative pressure is highly sensitive to the geometrical features of the porous nanostructures. Therefore, the key job when designing optimised nanostructures for enhancing nucleate boiling is to create optimal hybrid micro/nanostructures that can boost the generation of negative pressure, liquid supply towards and removal of vapor away from the nucleation sites.